ANALISIS PENGARUH PHYSICAL EVIDENCE DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA FOOD BOX KOTA BIMA - Amiruddin, Amiruddin; Nurdin, Herry (EKONOMI BISNIS, 2021)
This study aims to determine whether: 1) Physical evidence affects customer satisfaction, 2) Location affects customer satisfaction, 3) Physical evidence and location affects customer satisfaction at Cafe Food Box Bima City. The population in this study were all customers at the Cafe Food Box Kota Bima. The sampling technique used purposive sampling, data was obtained by distributing questionnaires to 100 respondents. The data analysis technique in this study was the validity test of the classical assumption test, the multiple linear regression test, the correlation test, the t and f determination test, using the spss 16.0 application. The results showed that: 1) Physical Evidence has a positive influence on customer satisfaction, 2) Location has a positive influence on customer satisfaction, 3) Physical evidence and location have a positive influence on customer satisfaction, the Cafe Food Box Kota Bima.